Contaminant Binding and Bioaccessibility in the Dust From the Ni‐Cu Mining/Smelting District of Selebi‐Phikwe (Botswana). (5th November 2022) - Ettler, Vojtěch; Hladíková, Karolína; Mihaljevič, Martin; Drahota, Petr; Culka, Adam; Jedlicka, Radim; Kříbek, Bohdan; Vaněk, Aleš; Penížek, Vít; Sracek, Ondra; Bagai, Zibisani
Abstract: We studied the dust fractions of the smelting slag, mine tailings, and soil from the former Ni‐Cu mining and processing district in Selebi‐Phikwe (eastern Botswana). Multi‐method chemical and mineralogical investigations were combined with oral bioaccessibility testing of the fine dust fractions (<48 and <10 μm) in a simulated gastric fluid to assess the potential risk of the intake of metal(loid)s contaminants. The total concentrations of the major contaminants varied significantly (Cu: 301–9, 600 mg/kg, Ni: 850–7, 000 mg/kg, Co: 48–791 mg/kg) but were generally higher in the finer dust fractions. The highest bioaccessible concentrations of Co, Cu, and Ni were found in the slag and mine tailing dusts, where these metals were mostly bound in sulfides (pentlandite, pyrrhotite, chalcopyrite). On the contrary, the soil dusts exhibited substantially lower bioaccessible fractions of these metals due to their binding in less soluble spinel‐group oxides. The results indicate that slag dusts are assumed to be risk materials, especially when children are considered as a target group. Still, this exposure scenario seems unrealistic due to (a) the fencing of the former mine area and its inaccessibility to the local community and (b) the low proportion of the fine particles in the granulated slag dump and improbability of their transport by wind. The human health risk related to the incidental ingestion of the soil dust, the most accessible to the local population, seems to be quite limited in the Selebi‐Phikwe area, even when a higher dust ingestion rate (280 mg/d) is considered. Plain Language Summary: The mining and processing of nickel‐copper ores in Selebi‐Phikwe (semi‐arid east of Botswana) left a legacy of various waste materials (mine tailings, slags) and contaminated soils. This study examines the forms of inorganic contaminants and their gastric bioaccessibility (defined as their fraction, which is soluble under the simulated gastric conditions) in the fine dust fractions, which could be wind‐eroded from the waste disposal sites or unvegetated topsoil. The bioaccessible concentrations of cobalt, copper, and nickel were higher for the slag and tailing dusts. In contrast, their bioaccessibility from the soil dusts was relatively low due to their binding in less soluble minerals. The exposure estimates were calculated for children and adults, assuming variable dust ingestion rates. Still, the daily intakes exceeded the guidelines only for the slag dust and, in the case of nickel, also for the tailing dust when children are considered as the target population. However, this exposure scenario seems improbable due to the fencing of the former mine area and its inaccessibility to the local community. Our findings demonstrate that the overall human health risk related to the contaminated dust ingestion seems quite limited in the Selebi‐Phikwe area. Key Points: Dust fractions (<48 and <10 μm) from slag, tailings, and soil near a Ni‐Cu mining district in Selebi‐Phikwe (Botswana) were studied Oral bioaccessibility of metals depends on mineralogy and is higher for slags and tailings (sulfides) than for the soil dust (spinels) Low exposure risk for the local population even when a high dust ingestion rate (280 mg/d) is considered